Treatment of hemangioma of the glans penis using Nd:Yag laser. Apropos of a case - Amaro, J. L. [UNESP]; Agostinho, A. D.; Polido Júnior, A.; Costa, R. P.; Trindade Filho, J. C.; Trindade, J. C. (Journal D'urologie, 1997)
Hemangioma of urinary tract are unusual, being about 2% of all hemangiomas. We present a case of a glans penis hemangioma. There is controversy concerning their treatment and outcome. Our patient was treated with a Neodymium: Yag laser irradiation, with complete morphological recuperation.